ANALISIS TERHADAP PARTISIPASI POLITIK MAHASISWA PADATINGKAT PENGAMAT DI UNIVERSITAS RIAU - Misra Nilfida; Sri Erlinda; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research in the background with the student movement as a representation of the political knowledge of students also assessed the more relegation evidenced by the low level of their role in the escort and the correct policy. Low level of political participation of students to make them feel not care because students are less concerned with political activities, as well as feeling busy with academic and Personal Affairs. As for problems this research is how political participation at the level of students at the university of riau?. The goal of this research is to know the political participation of students at the level of the university of riau. Based on the results of the study can be inferred that the percentage of recap of the respondents answer the poll about the analysis of political participation at the level of student at the university of riau, who said,